Are Content Marketing and Switching Barriers Decisive in Building Consumer Satisfaction, Trust and Loyalty on Ride-Hailing Services in Indonesia - Ramadania; Hartono; Juniwati; Hendra; Reswari, Rianti Ardana (The Asian Journal of Technology Management (AJTM), 2023)
Abstract. This study is aimed to investigate factors influencing customer loyalty of community-based ride-hailing service in Indonesia. More specifically, this study examines the relationship between content marketing, switching barriers, customer trust, and satisfaction toward customer loyalty. Data was collected through a survey of 180 respondents. Proposed hypothesis is tested using Partial Least Squares - Structural Equation Modelling. The variables in this study are content marketing and switching barriers as exogenous variables, trust and satisfaction as endogenous intervening variables and customer loyalty being final endogenous variables. The measurement scale uses a Likert scale from 1-5. The results show a positive influence between content marketing on customer trust and satisfaction, then there is also positive influence between satisfaction and trust on customer loyalty. However, switching barriers have no effect on trust, satisfaction, and loyalty of community-based ride hailing service users in Indonesia. The technique of collecting data through online media does not allow researchers to conduct in-depth interviews with respondents. Most of the existing research so far does not emphasize the importance of building loyalty through content marketing strategies. This study emphasizes the importance of content marketing strategies in building loyalty through intermediary satisfaction and trust in community-based ride hailing service businesses. Keywords: Content marketing, switching barriers, satisfaction, trust, loyalty, community-based ride hailing service.